Ethical Judgment and Whistleblowing Intention: Examining the Moderating Role of Locus of Control - Chiu, Randy K. (Journal of business ethics, 2003)
The growing body of whistleblowing literature includes many studies that have attempted to identify the individual level antecedents of whistleblowing behavior. However, cross-cultural differences in perceptions of the ethicality of whistleblowing affect the judgment of whistleblowing intention. This study ascertains how Chinese managers/professionals decide to blow the whistle in terms of their locus of control and subjective judgment regarding the intention of whistleblowing. Hypotheses that are derived from these speculations are tested with data on Chinese managers and professionals (n = 306). Statistical analysis largely supports the hypotheses, which suggests that an individual's locus of control does moderate the relationship between ethical judgment and whistleblowing.